POLA DETERMINASI PILIHAN DAN NILAI PADA TINDAKAN DISKRESI BIDAN ; STUDI PELAYANAN KESEHATAN IBU DAN ANAK - Alexsander Alexsander (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2019)
Since the problem of high mortality rate of mother and baby in the year of 2015 in Bengkulu City, the behavioral problem of the key actor in mother and baby health service delivery became an urgent discourse. This research aimed at identifying the self determinant pattern of midwife’s discretional action in the practice of service delivery. Qualitative aproach with action research design is implemented with midwife profession as the individual analysis unit. The key informan taken are qualified midwive and also supported by several multi actors informen. Research is held in six months . Data were collected by FGD and Indepth interview, observation, and document study. To obtain targeted result, data is analysed with inductive logic frame work.The research show the mother mortality is urgent problem in health service sector. As the result of the lack of human resources and over-workload, some of midewive develop the mechanism of procedure tightening. While, determinant behavior is accumulated in purpose of rasionalizing of sources as the result of unsufficient resources. Besides, in the pattern of decision makingsocial and safety reasons are shown as determinant factors. Those factors affected in midwife health service delivery.The contribution of the research is the exploration of determinat factors in optional discretion. Besides the further research map in the discourse of dicretion and street level bureaucrats.